APPLICATION OF CHI SQUARE TEST IN MARKETING RESEARCH - CODRUȚA DURA; IMOLA DRIGĂ (Annals of the University of Petrosani: Economics, 2017)
The paper brings into focus the usefulness of chi square test in the field of marketing research. A chi square test represents a statistical tool based on the chi-square distribution of probability, which is easy to apply by a non-mathematician researcher in order to provide an efficient business solution. Therefore, the paper discusses chi-square test requirements and methodology, along with conditions that determine the researcher in marketing to reject or to retain the null hypothesis. Further on, we aim at solving a specific marketing problem with the help of the chi-square test. Our approach involves both” the classical” procedure employed in order to apply a chi-square test and the modern way of finding the solution, which implies the involvement of the SPSS soft.